Riesgo de transmisión de bacterias portadoras de betalactamasas de espectro extendido en cirugía laparoscópica y su impacto en el equipo quirúrgico. - Lara Dutan, Angel Cristobal (2024)
During laparoscopic procedures, surgical personnel are exposed to various sources of bacterial contamination, including contact with the patient, instruments, and the surgical environment. However, the transmission of these resistant bacteria is not considered frequently enough. Therefore, the objective of this study was to investigate the risk of transmission of bacteria carrying extended-spectrum beta-lactamases during laparoscopic surgeries and understand its impact on the surgical team. For the analysis, a qualitative, descriptive and exploratory research was carried out using as a source of information scientific articles with a maximum of 5 years old, located in different scientific bases such as PubMed, Scopus, Web of Science, Cochrane Library, Google Scholar, Up to date, Science Direct among others. A total of 115 articles were obtained which, after applying a series of inclusion and exclusion criteria, allowed this number to be reduced to a final sample of 48 studies. The risk factors identified for the transmission of ESBL-producing bacteria to the surgical team during laparoscopic surgeries include: microperforations in gloves, high bacterial loads in professionals' beards, wet contacts in surgical clothing, bacterial load in the operating room air, surgical smoke . and fluid splashes from the patient. However, more research is needed in this field to quantify this risk.